‘Auf der Flucht’: the motif of flight in the works of Bertolt Brecht - Kuhn, T (Legenda, 2021)
The discourse of migration was prominent in Brecht’s time (as in our own), with vast and enforced population movements in Europe in the years following the First World War, and then again, across the globe, during European Fascism and the Second World War. My initial purpose in this essay was to interrogate Brecht’s perspective on the phenomenon but, as you will see, my findings took me somewhere rather different.¹ Refugees ‘in flight’ or ‘on the run’ are a common sight in Brecht’s writings of exile. He himself is ‘geflüchtet unter das dänische Strohdach’, as he says in the motto to...